Edukasi Protokol Kesehatan Untuk Pencegahan Penyebaran Penyakit Menular Monkeypox Pada Kelompok Lanjut Usia Di Sikumana Kupang - Pius Weraman; Muntasir Muntasir; Anderias Umbu Roga; Jacob M. Ratu; SP Manongga (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
This community service is aimed at providing education for community groups, especially for the elderly, to increase understanding of the health protocol for the Prevention of Infection Transmission (PPI). The activities including counseling and socializing about the Monkeypox for the community in Sikumana Village, distribution of leaflets, placing banners of the transmission prevention of Monkeypox, performing healthy elderly gymnastics, free examination and treatment for the target age community, and carry out GERMAS (Healthy Living Community Movement) in the form of proper and correct hand washing. This activity was attended by 48 participants. The evaluation results showed 100 percent of elderly participants were happy with this service activity. This activity has been provided knowledge and understanding of the PPI health protocol for the elderly.